Volatilization characteristics of high-lead slag and its influence on measurement of physicochemical properties at high temperature - Wang, Guohua; Cui, Yaru; Yang, Ze; Guo, Ziliang; Zhao, Lv; Li, Xiaoming; Zhao, Junxue; Tang, Wendan (Journal of mining and metallurgy. Section B, Metallurgy, 2020)
Volatilization causes measurement deviations of physicochemical properties for volatiles-containing slag at high temperature. Hence, investigating the degree of volatilization and identifying the volatilization mechanism and deviation rules are crucial to improve the accuracy of the measured properties. Here, PbO-FeOx-CaO-SiO2-ZnO slag system was selected as a research subject. The volatile characteristics and non-isothermal intrinsic kinetic models of high-temperature volatilization for lead slag were established by thermogravimetric analysis (TGA), and the volatilization mechanism and deviation in the measured properties were determined by analyzing the phase and chemical composition of the residues. In addition, experimental measurements of the melting temperature/ viscosity were compared with theoretically calculated results. The volatilization of PbO decreased the lead-containing phase, but increased the amount of precipitated spinel phase, which led to the deviation in the measured physicochemical properties of the studied slags. The volatilization kinetics for PbO in the slags followed three-dimensional diffusion. The diffusion of PbO gas from PbO-FeOx-CaO-SiO2-ZnO slag was the restrictive step of volatile reaction, and mechanism function was g(?)=1-(1-?)1?3. Moreover, during the slag properties measurement at high temperatures, a high heating rate and protective gas can be used to reduce volatilization of lead slag and avoid consequent properties deviation. nema